MR imaging features of Lhermitte–Duclos disease: Case reports and literature review. Issue 4 (28th January 2022) - Zhang, Han-wen; Zhang, Yuan-qing; Liu, Xiao-lei; Mo, Yong-qian; Lei, Yi; Lin, Fan; Feng, Yu-ning
Abstract: Rationale: Lhermitte–Duclos disease (LDD) is a rare tumor of the nervous system with a typical "tiger striped'" sign, but its features on functional magnetic resonance imaging (fMRI) are still inconclusive. Patient concerns: To explore the characteristics of LDDs using fMRI. Diagnoses: We report 3 cases of pathologically confirmed LDDs. Interventions: Three patients underwent brain tumor surgery. Outcomes: All the patients had a good prognosis. Lessons: Magnetic resonance spectroscopy and susceptibility-weighted imaging combined with conventional MRI can be used to better diagnose LDDs. Perfusion-weighted imaging is not specific for distinguishing cerebellar tumors. The combined application of fMRI and conventional MRI can improve the accuracy of LDD diagnoses.